ANALISIS KINERJA KEUANGAN PADA BANK PERKREDITAN RAKYAT (BPR) DI JAKARTA PUSAT PERIODE 2018 – 2020 - Marpaung, Oktavia (Jurnal Kewirausahaan Bukit Pengharapan, 2022)
This study aims to determine the effect of Capital Adequacy Ratio, Loan Deposit Ratio, Earning Asset Quality on financial performance. The population in this study were 13 PT. Rural Banks registered with the Financial Services Authority for the 2018-2020 period. The type of research used is descriptive research. The data collection technique used is the documentation method. Furthermore, the sampling technique used is purvosive sampling with a total sample of 12 samples from Rural Banks in the Central Jakarta Region registered with the Financial Services Authority (OJK). The data analysis technique used multiple linear regression analysis. The results of the third variable studied have the same results, where the Capital Adequacy Ratio (CAR) with a tcount value of 3,368 > a ttable value of 2.032, with a significance value of 0.002 <0.05, Loan Deposit Ratio (LDR) with a tcount value of 5.719 > 2.032 and a significance value of 0.000 <0.05 and Earning Asset Quality with a tcount of -2.637 < -2.032 and a significance value of 0.013 <0.05 simultaneously have a significant and significant effect on financial performance.